1999
DOI: 10.1016/s0167-2738(98)00415-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical blackening of yttria-stabilized zirconia – morphological instability of the moving reaction front

Abstract: Electrochemical reduction was performed on both polycrystals of calcia-stabilized zirconia (CSY) and single crystals of yttria-stabilized zirconia (YSZ) at 5008C. A glass-encapsulation was used to prevent access of molecular oxygen from the gas phase and to realize a virtually two-dimensional geometry for the reacting crystal. The resulting blackening process which occurs by the advancement of a morphologically unstable reaction front was observed in-situ in a heating-stage by the use of an optical microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
2
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 25 publications
7
153
2
5
Order By: Relevance
“…8. No zirconium was detected in the Fe melt and no blackening phenomena 13) was observed in the ZrO 2 .…”
Section: The Oxygen Depleted Layer At the Fe Melt/zromentioning
confidence: 86%
“…8. No zirconium was detected in the Fe melt and no blackening phenomena 13) was observed in the ZrO 2 .…”
Section: The Oxygen Depleted Layer At the Fe Melt/zromentioning
confidence: 86%
“…When a current of 10 A is applied between the Pt working electrode and the counter electrode, oxygen evolution is observed by MS at both temperatures. During the galvanostatic step, zirconia is electrochemically reduced at the cathode to release O 2− which migrates to the anode across YSZ according to reaction (R1) [16]. When the potential of Pt electrode (vs. gold reference) is higher than 300 mV [11], oxygen evolution takes place at the triple phase boundary (TPB) of the anode according to reaction (R2):…”
Section: Methodsmentioning
confidence: 99%
“…The observations were attributed to a significant component of electronic conduction as a result of the DC electric field. Earlier work by Janek and Korte 32) on the blackening of YSZ single crystals at the cathode under electrochemical reduction also concluded that the reduction led to a higher electronic conductivity than in the ionic conductivity of unreduced material. Darkening of YSZ due to reduction under flash sintering conditions has recently been observed by Morisaki et al 33) Darkening of the specimens near the cathode was also observed here and is not surprising given the difficulty of reducing sufficient atmospheric oxygen to maintain ionic conduction at the small contact area between the Pt electrode and the specimen in our specimens.…”
Section: Resistivity At High Currentsmentioning
confidence: 94%